Characterising the diversity and functional profiles of the rhizobiome in mixed dipterocarp forest - Ng, Yong Zhi (Nanyang Technological University, 2021)
The dominance of dipterocarps in South East Asia tropical forests has been long noted by many scholars and mycorrhizal association has been suggested to play a big role in this. However, genomic insights into this hypothesis have been lacking. In this study, first of its kind in Singapore, we use deep shotgun metagenomics to capture both bacterial and fungal diversity in bulk and root soil of three different species (Shorea curtisii, Shorea leprosula and Koompassia malaccensis) from Bukit Timah Nature Reserve. We found that bulk soil is distinct from root soil both in terms of taxonomical and functional profiles across all three species. Root soil samples can be separated by habitat preference between species, but not by taxonomic similarities. This separation is driven by the presence of different fungal species representing different types of mycorrhizal association. The diversity of root soil is also found to be significantly lower than the bulk counterpart. This pioneering study contributes to our understanding the microbial biodiversity in Singapore and South East Asia tropics in general and serves as a guideline for further studies to be conducted.